The Recreational Physical Activity from the Perspective of Mothers of Children with Autism Spectrum Disorder - Ezgi Ertüzün (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: In this research, we aim to investigate the evaluation of the Recreational Physical Activity Program participated by the children with Autism Spectrum Disorder from the perspective of mothers in Konya. Methods: For this aim, we conducted face to face interviews with 10 mothers and then a focus group with the same mothers to discuss our results. The data is analysed by using MAXQDA 2018 program. Results: It was emerged ‘life with Autism Spectrum Disorder through the eyes of mothers’ and ‘factors affecting mothers’ evaluations of the program’ as the main themes. Conclusion: Our results show that mothers perceive their life as a difficult and empowering struggle and mothers evaluated the program positively based on the impact of the program on the skill development of their children, the role of the trainer and the limited leisure activities of their children. Mother’s views of challenges and solutions mainly signify the need for increasing the number and accessibility of these centers and for designing programs both for children and for mothers.